The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1186/2192-0567-2-19
|View full text |Cite
|
Sign up to set email alerts
|

Nonindustrial private forest owners' opinions to and awareness of energy wood market and forest-based bioenergy certification - results of a case study from Finnish Karelia

Abstract: Background: Nonindustrial private forest owners (NIPFs) in Finland are important stakeholders of forest management and roundwood supply decisions. Their role will also be significant to supply energy wood to meet Finland's target for renewable energy in the future. The main objectives of this study were to explore the opinions and awareness of the Finnish NIPFs related to the energy wood market and forest-based bioenergy certification issues in Finland and their relevance for future bioenergy policies. Method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Although there have been studies in Europe and North America that investigated private land owners' perceptions of FBE (see [10][11][12][13][14][15][16]), their relevance in India is limited as private forest ownership is negligible in the country. Therefore, the studies conducted in Nepal and China to explore state forestry professionals' perceptions of energy production from forest biomass (see [17][18][19]) could be more relevant in an Indian context due to the similar type of dominating public forest ownership that exists in these countries.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although there have been studies in Europe and North America that investigated private land owners' perceptions of FBE (see [10][11][12][13][14][15][16]), their relevance in India is limited as private forest ownership is negligible in the country. Therefore, the studies conducted in Nepal and China to explore state forestry professionals' perceptions of energy production from forest biomass (see [17][18][19]) could be more relevant in an Indian context due to the similar type of dominating public forest ownership that exists in these countries.…”
Section: Discussionmentioning
confidence: 98%
“…Small-scale private forest owners (also known as non-industrial private forest owners, or NIPFs) play a major role in supplying forest biomass to the forest-based industries including the bioenergy industry in Finland, Sweden, and the US. Halder et al [10] conducted a study among the NIPFs in Finland to explore their perceptions of energy wood supply from their forests. The results showed that the Finnish NIPFs perceived the price of energy wood as the most important factor for them to decide if they supply energy wood from their forest estates and, since price of energy wood was not very attractive to them, they were not motivated to supply energy wood from their forest estates.…”
Section: Introductionmentioning
confidence: 99%
“…3. En Suède (Bohlin et Roos, 2002), Finlande (Rämö et al, 2009 ;Halder et al, 2012), Norvège (Brough et al, 2013), et Croatie-Serbie (Halder et al, 2014).…”
unclassified